Predictors of Limited Quantitative Methodology Use in Clinical Social Work Research: A Survey of Zimbabwean Social Work Students. - Muzingili, Taruvinga (Clinical Social Work Journal, 2025)
The study investigates factors contributing to the low level of skill in the adoption of quantitative approaches in clinical social work aligned students' thesis. We collected the data over a five-year period, spanning from 2019 to 2023. The data was collected from a sample of (n = 264) social work students who had completed a Bachelor of Social Work with Honors Degree or a Master of Social Work, all with research topics related to clinical social work. A self-administered questionnaire was used as a research instrument to measure the influence of four major items: attitudes and beliefs, knowledge and skills, institutional factors, and confidence, in predicting the adoption of quantitative approaches in clinical social work aligned students' thesis. A bivariate Pearson's correlation analysis showed that knowledge and skills had a moderately negative correlation at ρ < 0.05 with the use of quantitative approaches in social work students' thesis, while attitudes and beliefs, institutional factors, and confidence had a strong positive correlation (ρ < 0.01). A regression analysis showed that all major dimensions-attitudes and beliefs and knowledge and skills were both statistically significant at (ρ < 0.05), while institutional factors and confidence at ρ < 0.01. The 5th regression model combined all four factors, and the model was statistically significant at ρ < 0.01. The study called for clinical social work education and training to empower students to adopt a positive attitude towards quantitative research, foster a culture of institutional support and collaboration, and enhance students' confidence in conducting quantitative research.